2012
DOI: 10.1080/03055698.2011.567041
|View full text |Cite
|
Sign up to set email alerts
|

The mystery of student selection: are there any selection criteria?

Abstract: First-year students are still failing at an alarming rate. This is an international issue that universities face and there is currently no clear indication of the cause of the problem as universities move from being elite to providing mass education. This article examines the possible correlation between students' high school performance and first-year performance. The focus is primarily on the students' performance in mathematics and English. National Senior Certificate results as well as academic and mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Moreover, the results revealed that admission of graduate students from senior high school had been shown to improve the programme objectives of the computerized system for admission. The findings is similar to that of Marnewick [31]. Furthermore, the results of the study found that each student's record is personally checked at ease with the help of the computerized system to ensure that he/she fulfils the requirements for admission [47][48][49][50][51].…”
Section: Discussion Of Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Moreover, the results revealed that admission of graduate students from senior high school had been shown to improve the programme objectives of the computerized system for admission. The findings is similar to that of Marnewick [31]. Furthermore, the results of the study found that each student's record is personally checked at ease with the help of the computerized system to ensure that he/she fulfils the requirements for admission [47][48][49][50][51].…”
Section: Discussion Of Resultssupporting
confidence: 63%
“…The admission of students from senior high school has proven to enhance the programme's objectives [4], for example, because it brings unique perspectives that enrich students' experiences of education, the Admissions Committee can recognise the value of a diverse student body. Various backgrounds maybe also in terms of academic records, the rural upbringing of students, ethnic, social, and gender classifications [31]. The concept of affirmative action as in other countries such as the US, promotes diversity independent of candidate ranking [32].…”
Section: General Concerns About the Problem Of Student Selectionmentioning
confidence: 99%
“…Higher Education South Africa 2 commissioned the NBT in 2005, to complement the NSC results and to provide universities with information about first-year university students' entry-level skills [7,8]. The NBTs are written in the final year (grade 12) of the Further Education Training level by prospective university entrants, depending on the admission requirements of the degree they intend studying.…”
Section: Introductionmentioning
confidence: 99%
“…Given the need to improve the retention and throughput of South African medical students, it is imperative to understand the predictive validity of the NBT and NSC results as selection tools for entry into medical programmes. While many studies have investigated the predictive validity of the NSC [8,26,27] and the NBT [7,9], and the combined predictive validity of the NBT and the NSC [15,28] for student performance, such research has not been conducted for first-year South African medical students at Wits University. Understanding the link between students' performance in the NBT and the first year of the MBBCh degree will provide a measure of whether the combination of the NSC and NBT can discriminate between students with the potential to succeed academically and those without, to identify students [6] Higher Certificate Pass the NSC with at least a rating of 2 (30-39%) for the language of learning and teaching of higher education institutions.…”
Section: Introductionmentioning
confidence: 99%
“…The selected pre-admissions test was the HOAE exam (Health Occupation Aptitude Examination), a multiple choice examination that assesses student's skill and aptitude in English, math, critical thinking, and problem solving. Since past academic achievement in math and verbal ability are typically indicative of future college performance (Marnewick, 2012;Schmitt, 2012), these two topics were selected as the two essential components to be included in the HOAE test utilized by FAHCS at Sheridan College. The test is heavily utilized by many Colleges in Ontario as an entrance criterion for admissions into College-level Health Professional Programs.…”
Section: Introductionmentioning
confidence: 99%